Humidity-Controlling Ceramic Bricks: Enhancing Evaporative Cooling Efficiency to Mitigate Urban Heat Island Effect - Jin, Xueli; Wang, Junsong; Tan, Kanghao; Zou, Zhenjie (Atmosphere, 2024)
Passive evaporative cooling technology using the building envelope is a crucial measure to mitigate the urban heat island effect. This study aims to enhance the cooling efficiency of the surface of enclosure structures by utilizing volcanic ash, potassium–sodium stone powder, and silica-based mesoporous oxide (SMO) as primary materials. These components are incorporated into the ceramic brick production process to create innovative humidity-controlling ceramic bricks (HCCTs). This study extensively investigates the impact of SMO and the amount of applied glaze on the physical and mechanical characteristics of these HCCTs. Additionally, it examines the water absorption and evaporative cooling properties of the studied materials under optimal substitution conditions. Numerical calculations are used to determine the heat and moisture transfer properties of HCCTs. The results indicate that incorporating 2% SMO and applying 70 g/m2 of glaze results in a moisture absorption capacity of 385 g/m2 and a moisture discharge capacity of 370 g/m2. These conditions also yield a notable flexural strength of 15.2 MPa. Importantly, the HCCTs exhibit significantly enhanced capillary water absorption and water retention capabilities. Increased water absorption reduces surface temperature by 2–3 °C, maintaining the evaporative cooling effect for 20 to 30 h. It is also found that the temperature of HCCTs decreases linearly with increasing water content and porosity, while the temperature difference gradually decreases with thickness. Water migration in HCCTs with greater thickness is notably influenced by gravity, with water moving from top to bottom. Therefore, it is recommended that brick thickness does not exceed 15 mm.